Diagnostic Performance of Rectal CT for Staging Rectal Cancer: Comparison with Rectal MRI and Histopathology - Seok Yoon Son; Yun Seok Seo; Jeong Hee Yoon; Bo Yun Hur; Jae Seok Bae; Se Hyung Kim (Journal of the Korean Society of Radiology, 2023)
Purpose To compare the diagnostic performance of rectal CT with that of high-resolution rectal MRI and histopathology in assessing rectal cancer. Materials and Methods Sixty-seven patients with rectal cancer who underwent rectal CT with rectal distension using sonographic gel and high-resolution MRI were enrolled in this study. The distance from the anal verge/anorectal junction, distance to the mesorectal fascia (MRF), extramural depth (EMD), extramesorectal lymph node (LN) involvement, extramural venous invasion (EMVI), and T/N stages in rectal CT/MRI were analyzed by two gastrointestinal radiologists. The CT findings of 20 patients who underwent radical surgery without concurrent chemoradiotherapy were compared using histopathology. Interclass correlations and kappa statistics were used. Results The distance from the anal verge/anorectal junction showed an excellent intraclass correlation between CT and MRI for both reviewers. For EMD, the distance to the MRF, presence of LNs, extramesorectal LN metastasis, EMVI, T stage, and intermodality kappa or weighted kappa values between CT and MRI showed excellent agreement. Among the 20 patients who underwent radical surgery, T staging, circumferential resection margin involvement, EMVI, and LN metastasis on rectal CT showed acceptable concordance rates with histopathology. Conclusion Dedicated rectal CT may be on par with rectal MRI in providing critical information to patients with rectal cancer.